Free Model of Sentence Classifier for Automatic Extraction of Topic Sentences - M.L. Khodra; D.H. Widyantoro; E.A. Aziz; B.R. Trilaksono (LPPM ITB, 2011)
This research employs free model that uses only sentential features without paragraph context to extract topic sentences of a paragraph. For finding optimal combination of features, corpus-based classification is used for constructing a sentence classifier as the model. The sentence classifier is trained by using Support Vector Machine (SVM). The experiment shows that position and meta-discourse features are more important than syntactic features to extract topic sentence, and the best performer (80.68%) is SVM classifier with all features.